2016
DOI: 10.4049/jimmunol.1501261
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Intake of Dietary Lipids Alters Membrane Structure and T Cell Responses in LDLr−/− Mice

Abstract: Although it is recognized that lipids and membrane organization in T cells affect signaling and T cell activation, to what extent dietary lipids alter T cell responsiveness in the absence of obesity and inflammation is not known. In this study, we fed low-density lipoprotein receptor knockout mice a Western high-fat diet for 1 or 9 wk and examined T cell responses in vivo along with T cell lipid composition, membrane order, and activation ex vivo. Our data showed that high levels of circulating lipids for a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 65 publications
3
13
0
Order By: Relevance
“…Moreover, the pain-modulatory effects of the high-fat diet apparently take some time to develop, since we could not fully mimic the pain phenotype by providing this diet for only one week prior to implementing the DRG inflammation model. Similar to this finding, a study in mice genetically engineered to respond to a high-fat diet with elevated cholesterol and blood lipids, but not increased body weight, found that the observed effects of diet on T cell function required many weeks to develop even though blood cholesterol and lipids were markedly elevated within one week 49 . Collectively, this suggests that high-fat diet may alter immune system function through a process that takes several weeks to develop, and that can sometimes be dissociated from any effects on body weight and adiposity.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Moreover, the pain-modulatory effects of the high-fat diet apparently take some time to develop, since we could not fully mimic the pain phenotype by providing this diet for only one week prior to implementing the DRG inflammation model. Similar to this finding, a study in mice genetically engineered to respond to a high-fat diet with elevated cholesterol and blood lipids, but not increased body weight, found that the observed effects of diet on T cell function required many weeks to develop even though blood cholesterol and lipids were markedly elevated within one week 49 . Collectively, this suggests that high-fat diet may alter immune system function through a process that takes several weeks to develop, and that can sometimes be dissociated from any effects on body weight and adiposity.…”
Section: Discussionsupporting
confidence: 55%
“…ref. 49 ). Human studies indicate that systemic elevation of these markers may depend on the degree of metabolic dysregulation and/or the specific deposition of adipose tissue (e.g., visceral vs. subcutaneous) rather than on total adiposity per se 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the fact that DHA has been shown to significantly alter plasma membrane lipid raft composition [136,138], our lab recently demonstrated that n-3 PUFA alter EGFR lipid raft localization and HRAS, KRAS and NRAS activation [181]. These findings can be attributed to the fact that prolonged intake of dietary lipids modifies membrane order[183]. Interestingly, other MTDB’s, e.g., curcumin, have been shown to alter localization of α6β4/EGFR to lipid rafts[184].…”
Section: Introductionmentioning
confidence: 55%
“…The data qualitatively and quantitatively demonstrate that lowering (18:2) 4 CL content led to the formation of smaller domains on a micron scale compared to higher (18:2) 4 CL levels. This suggests that domain size is tunable by CL levels analogous to studies on cholesterol and lipid rafts [74]. It is important to note that the loss of (18:2) 4 CL content on microdomain size was equivalent to the effect of replacing (18:2) 4 CL with (14:0) 4 CL.…”
Section: 0 Discussionmentioning
confidence: 84%